Common factor first
x³ + 7x² - 8x = 0
x(x² + 7x - 8) = 0
the first term x² = 1
The middle term inside the parenthesis is + 7x
Find the sum of the middle term
multiply the first term 1 times the last term 8 equals 8 and factor
factors of 8
1 x 8. . .<=. .use these factors
2 x 4
+ 8 and - 1 satisfy the sum of the middle term
- 1 = - x
insert + 8x and - x into the equation
x(x² + 7x - 8) = 0
Group factor
x(x² + 8x - x - 8) = 0
x[x(x + 8) - 1(x + 8) = 0
x(x - 1)(x + 8) = 0
- - - - - -
Roots
x = 0
- - - - - -
Roots
x - 1 = 0
x - `1 + 1 = 0 + 1
x = 1
- - - - - - -
Roots
x + 8 = 0
x + 8 - 8 = 0 - 8
x = - 8
- - - - - - - s-
2007-06-02 07:00:18
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
For both problems, just divide through by x first. When we do that, for problem #1 we get this:
(x³ + 7 x² - 8 x) / x = x² + 7 x - 8.
x² + 7 x - 8 is factorable into (x - 1)(x + 8).
To find possible zeros, set all the factors equal to zero and then solve for x:
x = 0, since x is a factor, because we divided through by x first.
x - 1 = 0 ----> x = 1
x + 8 = 0 ----> x = -8.
So, x = 0, x = 1, or x = -8 are the answers for this problem.
For problem #2, first move 18x to the left side of the equation. When we do that, it becomes -18x, resulting in this final form:
2 x³ + 9 x² - 18 x = 0.
Then, when we divide through by x, we get this quotient:
2 x² + 9 x - 18, which is factorable into (2 x - 3)(x + 6). Now, we set all these factors equal to 0 and solve for x:
x = 0 for the same reason as problem #1
2 x - 3 = 0 ----> 2 x = 3 ----> x = 3/2
x + 6 = 0 ----> x = -6.
So, x = 0, x = 3/2, or x = -6 are the answers for problem #2.
2007-06-02 13:51:59
·
answer #2
·
answered by MathBioMajor 7
·
0⤊
0⤋
1. Factor out an x: x(x^2+7x-8)=0
then factor the parenthases: x(x+8)(x-1)=0
then set each factor equal to 0
x=0 x+8=0 x-1=0
then solve each equation for x
x=0 x=-8 x=1
2. Set equation equal to 0: 2x^3+9x^2-18x
then follow the same steps as number one:
x(2x^2+9x-18)=0
x(2x-3)(x+6)=0
x=0 2x-3=0 x+6=0
x=0 x=3/2 or 1.5 x=-6
2007-06-02 13:29:26
·
answer #3
·
answered by Delynn 2
·
0⤊
0⤋
x^3+7x^2-8x = 0
x(x^2+7x-8)=0 (take out x which is common)
x(x^2-x+8x-8) = 0 (7x can be rewritten as -x+8x)
x(x(x-1)+8(x-1))=0 (x is common from first 2 terms and 8 is common from last 2 terms)
x(x-1)(x+8)=0 (x-1) is common which leaves behind (x+8)
so answers are
x = 0, x = 1, x = -8
-----------------------------------------------------------------------------------
2x^3+9x^2= 18x
x(2x^2+9x-18) = 0 (bring 18x on LHS and so the sign changes to -ve and take out x which is common)
x(2x^2+12x-3x-18)=0 (9x can be rewritten as 12x-3x)
x(2x(x+6)-3(x+6))=0 (2x is common from first 2 terms and -3 is common from last 2 terms)
x (x+6)(2x-3) = 0 (x+6 is common which leaves (2x-3))
x = 0, x = -6, x = 3/2
2007-06-02 13:30:26
·
answer #4
·
answered by Sam 2
·
0⤊
0⤋
x^3+7x^2-8x=0
=>x(x^2+7x-8)=0
=>x{x^2-x+8x-8)=0
=>x{x(x-1)+8(x-1)}=0
=>x(x-1)(x+8)=0
=>x=0,1 or -8
2.2x^3+9x^2=18x
=>2x^3+9x^2-18x=0
=>x(2x^2+9x-18)=0
=>x(2x^2+12x-3x-18)=0
=> x{2x(x+6)-3(x+6)}=0
=> x(x+6)(2x-3)
Therefore either x=0 or -6 or 3/2
2007-06-02 13:25:02
·
answer #5
·
answered by alpha 7
·
0⤊
0⤋
1. Answer: 1, -8, 0
2. Answer: -6, 3/2, 0
Just trust me on this one.
2007-06-02 13:25:39
·
answer #6
·
answered by Life Is Beautiful at Sixx: A.M. 3
·
0⤊
0⤋